THE PERMIAN VOLCANICS OF CENTRAL ALBORZ: IMPLICATIONS FOR PASSIVE CONTINENTAL MARGIN ALONG THE SOUTHERN BORDER OF PALEOTETHYS - Delavari, Morteza; Dolati, Asghar; Mohammadi, Ali; Rostami, Farzaneh (Ofioliti, 2016)
The Permian volcanics of Central Alborz (PVCA) crop out between the Ruteh and Nesen Formations in the Baladeh-Siahbisheh area. The volcanics are predominantly basaltic and plagioclase-phyric. Ferromagnesian minerals such as clinopyroxene and olivine are not modally abundant and sometimes are totally altered. Chemical composition of clinopyroxene is characterized by high TiO2 contents (4.9-7.2 wt.%). Based on whole rock geochemistry, the samples display sodic alkaline nature (Na2O = 3.7 to 7.8 wt.%). Chondrite-normalized rare earth element (REE) patterns are extremely LREE-enriched with (La/Yb)N of 8.3-20.5. Both normalized REE and multi-element diagrams represent ocean island basalt (OIB) characteristics. Modeling based on trace element values, and the content of some major elements reveal low partial melting degree (< 10%) of a deep garnet-bearing mantle source. As the samples geochemically show an intra-plate tectonomagmatic setting without subduction zone signatures, during the Permian (and earlier times), the Alborz area was possibly a passive continental margin along the southern border of Paleotethys. As a result, the Alborz Permian magmatism could have been reasonably induced by an extensional tectonic regime along the northward-moving Cimmerian terranes during the early stages of Neotethys development.